2021
DOI: 10.1017/s1049096520002036
|View full text |Cite
|
Sign up to set email alerts
|

The Great Equalizer? Gender, Parenting, and Scholarly Productivity During the Global Pandemic

Abstract: Has the global COVID-19 pandemic negatively impacted the scholarly productivity of academics? Do gender and parenting magnify its effect? To obtain insight into the changes the pandemic has wrought in the lives and careers of women and parents in academia, we surveyed scholars in political science and international studies. The survey was in the field during the period in which many academics were experiencing shelter-at-home orders and adjusting to a new reality. It captures initial reactions to changed circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 8 publications
0
35
0
1
Order By: Relevance
“…Whereas ample evidence exists on the pre-pandemic gender gap in academia (Barnes and Beaulieu 2017;Chávez and Mitchell 2020;Dion, Sumner, and Mitchell 2018;Dolan and Lawless 2020;Hesli, Lee, and Mitchell 2012;Mitchell and Hesli 2013;Teele and Thelen 2017), we continue to learn more on post-pandemic gender disparities from journal submissions data (Wiegard et al 2020), funded grant proposals, and published research (Flaherty 2020;Kim and Patterson 2020;Kramer 2020). The abrupt shift in instruction modes, advising and mentoring, collaborative work, fieldwork plans, and research dissemination following the mandated lockdowns substantively impacted scholars' productivity, especially women with young children (Breuning et al 2021). Most recent work has shown that although both men and women with children experienced an increase in time dedicated to childcare, women reported disproportionately larger increases in childcare and decreases in time dedicated to research (Deryugina, Shurchkov, and Stearns 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas ample evidence exists on the pre-pandemic gender gap in academia (Barnes and Beaulieu 2017;Chávez and Mitchell 2020;Dion, Sumner, and Mitchell 2018;Dolan and Lawless 2020;Hesli, Lee, and Mitchell 2012;Mitchell and Hesli 2013;Teele and Thelen 2017), we continue to learn more on post-pandemic gender disparities from journal submissions data (Wiegard et al 2020), funded grant proposals, and published research (Flaherty 2020;Kim and Patterson 2020;Kramer 2020). The abrupt shift in instruction modes, advising and mentoring, collaborative work, fieldwork plans, and research dissemination following the mandated lockdowns substantively impacted scholars' productivity, especially women with young children (Breuning et al 2021). Most recent work has shown that although both men and women with children experienced an increase in time dedicated to childcare, women reported disproportionately larger increases in childcare and decreases in time dedicated to research (Deryugina, Shurchkov, and Stearns 2021).…”
mentioning
confidence: 99%
“…This article presents early evidence of the pandemic’s gendered effect on scholars in the discipline using online survey data and data from semi-structured interviews with female political scientists. Unlike recent work explicating the gender differential effect of the pandemic by focusing on women in academia more generally (Deryugina, Shurchkov, and Stearns 2021) or on a narrow focus of scholars’ individual productivity (Breuning et al 2021), our study uses a mixed-method approach to data collection and analysis. It also provides a more comprehensive view of the effects of the pandemic on scholars’ productivity, teaching, and non-research-related activities.…”
mentioning
confidence: 99%
“…Women faculty, and particularly women of color faculty, are no exception to this gendered norm (Bingham & Nix, 2010;Carr et al, 1998;Gunter & Stambach, 2003;Hart, 2016). Prior to and through the COVID-19 pandemic, many BIPOC women faculty have been responsible for childcare, homeschooling of children, or caretaking of aging family members, a responsibility that differentially impacts the productivity of women over men (Breuning et al, 2021;Cress & Hart, 2009;Krukowski et al, 2021). Throughout the pandemic, distinctions between work life and home life have been blurred (Shillington et al, 2020) as faculty offer online Zoom classes and participate in service committees from their living rooms, sometimes while also providing care for family members or coordinating their children's online schooling at home.…”
Section: Bipoc Women Carry the University's Emotional Labormentioning
confidence: 99%
“…Men+ have reported experiencing what we term "gender shock," or the sudden awareness of the depth of cognitive and emotional labor and active caregiving typically borne by women+ in the home (Windsor & Crawford, 2021). The burden of women+'s labor has grown on the same exponential curve as Covid-19 cases in the U.S. (Breuning et al, 2021) We focus in our research on the Academic Chutes & Ladders, the very real inequities and vulnerabilities that make it more difficult for women+ and parents of all genders to ascend the ranks of the academic profession (Crawford & Windsor, 2020a). Figure 1 demonstrates a hypothetical path from graduate school to tenure that illustrates how family formation in a nonpandemic year can affect the academic trajectory.…”
Section: Differential Effects Of Pandemic Parentingmentioning
confidence: 99%